ANALYSIS OF THE USE OF THE MINISTRY OF LAW AND HUMAN RIGHTS’ SIMPEG APPLICATION INFLUENCES THE DIRECTORATE GENERAL OF IMMIGRATION’S PERSONNEL ADMINISTRATION SERVICES AT ONE OF THE IMMIGRATION OFFICES - Budiarti, Isniar; Muhammad, Faridz (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to implement a management information system based on the SIMPEG application in providing services to the community. This research used a sample of 54 respondents at one of the directorates general of immigration at the Immigration Office. This research uses simple linear regression analysis and non-probability sampling techniques are used in the sampling method by collecting data through questionnaires, interviews and observation. The results obtained by the personnel management information system (SIMPEG) have a positive and significant effect on the personnel administration services of the Directorate General of Immigration at one of the Immigration Offices. This is because the resulting data reporting is in accordance with requirements. Apart from that, data in SIMPEG can be searched easily and the facilities available in SIMPEG are easy for employees to use, so that personnel administration services are better